Windows forensic analysis DVD toolkit 2E - Carvey, Harlan A. (Syngress Pub., 2009)
"Author Harlan Carvey has brought his best-selling book up-to-date to give you: the responder, examiner, or analyst the must-have tool kit for your job. Windows is the largest operating system on desktops and servers worldwide, which mean more intrusions, malware infections, and cybercrime happen on these systems. Windows Forensic Analysis DVD Toolkit, 2E covers both live and post-mortem response collection and analysis methodologies, addressing material that is applicable to law enforcement, the federal government, students, and consultants"--Resource description page.